Nonlocal problem for a single fourthorder equation (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
This paper examines a nonlocal problem for a single fourth-order equation. If some conditions are met, the existence and uniqueness of the solution of the problem are proved on the right side of the equation.